Putative P1B-type ATPase from the bacterium Achromobacter xylosoxidans A8 alters Pb2+/Zn2+/Cd2+-resistance and accumulation in Saccharomyces cerevisiae - Suman, Jachym; Kotrba, Pavel; Macek, Tomas (Biochimica et biophysica acta, 2014)
PbtA, a putative P(1B)-type ATPase from the Gram-negative soil bacterium Achromobacter xylosoxidans A8 responsible for Pb(2+)/Zn(2+)/Cd(2+)-resistance in Escherichia coli, was heterologously expressed in Saccharomyces cerevisiae. When present in Zn(2+)- and Pb(2+)/Cd(2+)-hypersensitive S. cerevisiae strains CM137 and DTY168, respectively, PbtA was able to restore Zn(2+)- and Pb(2+)-resistant phenotype. At the same time, the increase of Pb, Zn, and Cd accumulation in yeast was observed. However, Cd(2+)-tolerance of the pbtA-bearing yeasts dramatically decreased. The PbtA-eGFP fusion protein was localized primarily in the tonoplast and also in the plasma membrane and the perinuclear region corresponding to the endoplasmic reticulum at later growth stages. This indicates that PbtA protein is successfully incorporated into membranes in yeasts. Since PbtA caused a substantial increase of Pb(2+)/Zn(2+)-resistance and accumulation in baker's yeast, we propose its further use for the genetic modification of suitable plant species in order to obtain an effective tool for the phytoremediation of sites polluted by toxic transition metals.
Keywords: bakteriální proteiny; Saccharomyces cerevisiae; Bacterial Proteins; Lead; zinek; Achromobacter denitrificans; Zinc; Endoplasmic Reticulum; endoplazmatické retikulum; olovo; buněčná membrána; Adenosine Triphosphatases; kadmium; adenosintrifosfatasy; Cell Membrane; Cadmium